Alterations in the iron homeostasis network: A driving force for macrophage-mediated hepatitis C virus persistency. Issue 6 (17th August 2016) - Foka, Pelagia; Dimitriadis, Alexios; Karamichali, Eirini; Kyratzopoulou, Eleni; Giannimaras, Dionyssios; Koskinas, John; Varaklioti, Agoritsa; Mamalaki, Avgi; Georgopoulou, Urania
ABSTRACT: Mechanisms that favor Hepatitis C virus (HCV) persistence over clearance are unclear, but involve defective innate immunity. Chronic infection is characterized by hepatic iron overload, hyperferraemia and hyperferittinaemia. Hepcidin modulates iron egress via ferroportin and its storage in ferritin. Chronic HCV patients have decreased hepcidin, while HCV replication is modified by HAMP silencing. We aimed to investigate interactions between HCV and hepcidin, during acute and chronic disease, and putative alterations in cellular iron homeostasis that enhance HCV propagation and promote viral persistence. Thus, we used HCV JFH-1-infected co-cultures of Huh7.5 hepatoma and THP-1 macrophage cells, HCV patients' sera and Huh7 hepcidin-expressing cells transfected with HCV replicons. Hepcidin levels were elevated in acutely infected patients, but correlated with viral load in chronic patients. HAMP expression was up-regulated early in HCV infection in vitro, with corresponding changes in ferritin and FPN. Hepcidin overexpression enhanced both viral translation and replication. In HCV-infected co-cultures, we observed increased hepcidin, reduced hepatoma ferritin and a concurrent rise in macrophaghic ferritin over time. Altered iron levels complemented amplified replication in hepatoma cells and one replication round in macrophages. Iron-loading of macrophages led to enhancement of hepatic HCV replication through reversed ferritin "flow." Viral transmissibility from infected macrophages to naïve hepatoma cells was induced by iron. We propose that HCV control over iron occurs both by intracellular iron sequestration, through hepcidin, and intercellular iron mobilisation via ferritin, as means toward enhanced replication. Persistence could be achieved through HCV-induced changes in macrophagic iron that enhances viral replication in these cells.